Severe focal myelopathy secondary to chronic compression by an arachnoid pseudocyst in a Rottweiler - POLIZOPOULOU (Ζ.Σ. ΠΟΛΥΖΟΠΟΥΛΟΥ) Z. S.; SOUFTAS (Β.Δ. ΣΟΥΦΤΑΣ) V. D.; BRELLOU (Γ. ΜΠΡΕΛΛΟΥ) G.; PATSIKAS (Μ.Ν. ΠΑΤΣΙΚΑΣ) M. N.; SOUBASIS (Ν. ΣΟΥΜΠΑΣΗΣ) Ν.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ) A. F. (Journal of the Hellenic Veterinary Medical Society, 2017)
A four-year old Rottweiler was presented with tetraplegia, established progressively over a 4-month period. Initiallythe dog developed paresis of the posterior limbs that subsequently evolved to tetraparesis and finally tetraplegia. Upon neurological examination the dog exhibited spastic tetraplegia with exaggerated spinal reflexes in all four limbs. The neuroanatomical lesion localization indicated a focal or diffuse cervical spinal cord disease. Cisternal myelography revealed obstruction of the contrast medium flow at the level of C5 vertebral body. Magnetic resonance imaging disclosed intradural-extramedullary compression of the spinal cord at the level of C5-C6 intervertebral disc by a spinal arachnoid pseudocyst, syrinx formation and myelopathy expressed as abnormally higher signal on T2-weighted images at the C5 segment level. Severe demyelination, involving exclusively the white matter of the grossly affected segments and extending rostrally into the brainstem and caudally into the thoracic spinal cord segments, was noticed on histopathology. The unusually severe secondary degenerative change in the cervical spinal cord white matter, inflicted by focal SAP compression, was the most interesting finding.